The Effect of Perceived Ease of Use and Security on Trust Through User Satisfaction of Ovo E-Wallet in Medan City - Ivo Arfiani Turnip; Endang Sulistya Rini; Fadli (Indonesian Journal Publisher, 2026)
The rapid development of information technology has driven a transformation in payment systems toward digital transactions through the use of e-wallets. The OVO application has become one of the most widely used digital payment services among the public, including in Medan City. However, the use of such services is still influenced by various factors, such as perceived ease of use, security, user satisfaction, and trust. This study aims to analyze the effect of perceived ease of use and security on user trust in the OVO application, with user satisfaction acting as an intervening variable. This research employs a quantitative approach with an associative research design. The population of this study consists of OVO users in Medan City, categorized as an infinite population. The sample was determined using purposive sampling, with the criteria of active OVO users who have conducted transactions. The sample size was calculated based on five times the number of research indicators (27 items × 5), resulting in 135 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software The results indicate that perceived ease of use has a positive and significant effect on both trust and user satisfaction of the OVO e-wallet. In contrast, security does not have a significant effect on user trust but has a positive and significant effect on user satisfaction. Furthermore, user satisfaction has a positive and significant effect on user trust. Indirectly, user satisfaction is proven to mediate the effects of perceived ease of use and security on user trust in the OVO e-wallet.